PENGUNGKAPAN DIRI DI DUNIA MAYA DAN KEKERASAN TERHADAP PEREMPUAN - Rozi Sastra Purna; Sartana Sartana; Tryanda Millenia; Fauziah Afrilda (Kafa`ah: Journal of Gender Studies, 2021)
Abstract: The Internet has not become yet a secure world for women. Many women become targets of violence in cyberspace. The willingness of women to respond, introduce, and open up themselves to strangers on the internet causes this violence. The purpose of this research is to explore the process of self-disclosure of adolescent girls in cyberspace. Including the factors that influence, both supporting and obstacle. This research presents an in-depth review of the process of self-disclosure of women when they interact in cyberspace based on a literature review and theoretical analysis. The results of this research indicate that violence against women is transformed in a new form. One of the reasons for this phenomenon of violence is the victim's lack of carefulness when interacting in cyberspace. They are easy to open up and trust the people they know in cyberspace.